The End TB Strategy towards TB elimination 2 - Raviglione, Mario (Henry Stewart Talks, 2021)
Tuberculosis, The End TB Strategy, Rapid molecular diagnostic testing, Drug resistant TB, Drug susceptibility testing, TB and HIV, Latent TB, BCG vaccination, Universal health, TB and COVID-19